1990
DOI: 10.1016/0014-5793(90)80989-v
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases from human bone marrow stromal cell line KM 102 has erythroid‐potentiating activity, suggesting its possibly bifunctional role in the hematopoietic microenvironment

Abstract: In this study, we demonstrated that tissue inhibitor of metalloproteinases (TIMP) produced by human bone marrow stromal cell line KM-102 had erythroid-potentiating activity (EPA) which stimulates the proliferation of erythroid progenitor cells. We, then, propose a scheme for the bifunctional role of TIMP/EPA in hematopoietic microenvironment, that is, the maintenance of the integrity of bone marrow matrix and the proliferation of erythroid progenitor cells proceeding on the matrix.Tissue inhibitor of metallopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…4 To what extent the pleiotropic effects of TIMP-1 produced in the hematopoietic microenvironment influence normal hematopoiesis and/or the development of hematological malignancies remains unknown. Our results attempt to evidence that TIMP-1, as a BM microenvironment constituent, is involved in the erythroid cell physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 To what extent the pleiotropic effects of TIMP-1 produced in the hematopoietic microenvironment influence normal hematopoiesis and/or the development of hematological malignancies remains unknown. Our results attempt to evidence that TIMP-1, as a BM microenvironment constituent, is involved in the erythroid cell physiology.…”
Section: Discussionmentioning
confidence: 99%
“…2 Besides their MMPs inhibitory activity, TIMPs and in particular TIMP-1 exhibit other biological functions in cell survival, differentiation and proliferation. 3 TIMP-1 has first been described for its erythroid potentiating activity and then proposed as an important regulator of erythropoiesis 4 able to stimulate the proliferation of K562 leukemia cells 5 and both early and late erythroid committed stem cells from human bone marrow (BM). 6 However, Hayakawa et al 7 have demonstrated that TIMP-1 also exhibited mitogenic activity in other cells and proposed TIMP-1 as a new cell-growth factor.…”
Section: Introductionmentioning
confidence: 99%
“…TIMPs are believed to play a role in such diverse phenomena as erythropoiesis (Gasson et al, 1985;Hayakawa et al, 1990;Stetler-Stevenson et al, 1992b), bone resorption (Hill et al, 19931, ovulation (Curry et al, 19901, placentation (Lala and Graham, 1990;Graham and Lala, 19911, mammary gland involution (Talhouk et al, 1992), arthritic destruction of cartilage (Pelletier et al, 1990;Dean et al, 1989b) and the local and systemic spread of malignant tumors (Liotta and Stetler-Stevenson, 1990). High levels of TIMP-1 in the corpus luteum of pregnancy may play a role in the maintenance of pregnancy (Nomura et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition to blocking MMP activity, TIMPs have also been shown to exert growth factor activities that are independent of their enzymatic inhibitory function. [4][5][6][7][8][9][10] We have previously reported on the high-level expression of TIMP-1 by normal activated tonsillar B cells and centroblast-like Burkitt lymphoma cell lines. 11 TIMP-1 expression is operative at a specific stage in B-cell development and is associated with the germinal center phenotype that occurs with the generation of lymphoblasts.…”
Section: Introductionmentioning
confidence: 99%